Public Investment: Some Measuring Instruments - Sharma, Sharad (Tribhuvan University Journal, 2011)
Not available. Key words: Investment decisions; Scarcity of resources; Economy; Nepal Tribhuvan University Journal Vol XXI, No. 2, 1998 Page: 35-46 Uploaded date: 22 April, 2011